STUDY OF NGSO VHTS SATELLITE SYSTEM FOR BROADBAND CONNECTIVITY IN INDONESIA - Rama Setya Anggara; Heroe Wijanto; Budi Syihabuddin (RADJA PUBLIKA, 2026)
Indonesia’s archipelagic geography, uneven population distribution, and limited terrestrial infrastructure present persistent challenges to achieving inclusive and sustainable broadband connectivity. These constraints contribute to the digital divide, limiting access to digital public services. This study examines a Ka-band Very High Throughput Satellite (VHTS) system implemented in a Non-Geostationary Satellite Orbit (NGSO) Low Earth Orbit (LEO) constellation specifically tailored for tropical regions. The work combines orbital modeling, Ka-band link budget analysis, multibeam capacity evaluation, and rain attenuation mitigation. A 400 km LEO altitude gives the best balance between coverage, latency, and performance, with round-trip delays of about 3.5–4 ms. Automatic Transmit Power Control (ATPC) and adaptive phased array beamforming maintain the link availability even in severe tropical rain, which reduces the signal by more than 12 dB. A staggered national deployment plan shows that NGSO-VHTS systems can be used for broadband access and future 5G/6G Non-Terrestrial Networks (NTNs) in Indonesia.